2021
DOI: 10.3897/rrpharmacology.7.63059
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of carbamylated darbepoetin and udenafil in ischemia-reperfusion of rat kidney due to the effect of preconditioning and inhibition of nuclear factor kappa B

Abstract: Introduction: Acute kidney injury is a widespread complication in hospitalized patients, with a high mortality rate and long-term complications affecting prognosis and quality of life and with high human and financial costs. In addition, to date, no clear algorithm for the prevention of this type of damage has been developed. Materials and methods: The research was carried out on male Wistar rats. A 40-minute renal ischemia-reperfusion model was used to model acute kidney injury. Further, the renopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…One of the key mechanisms for the realization of their protective effects, researchers call the activation of the reverse tubuloglomerular connection, which leads to a decrease in hyperfiltration, one of the key pathogenetic links of kidney injury in diabetes mellitus, chronic kidney disease, and arterial hypertension 17, 28 . On the contrary, tubuloglomerular feedback is one of the components damaging kidney tissue in ischemic and reperfusion injuries, as it leads to glomerular vasospasm, which makes a significant contribution to the decrease in GFR in AKI 29 . In this regard, it was suggested that SGLT-2 inhibitors may increase the risk of developing AKI, which has been demonstrated in some studies 28 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the key mechanisms for the realization of their protective effects, researchers call the activation of the reverse tubuloglomerular connection, which leads to a decrease in hyperfiltration, one of the key pathogenetic links of kidney injury in diabetes mellitus, chronic kidney disease, and arterial hypertension 17, 28 . On the contrary, tubuloglomerular feedback is one of the components damaging kidney tissue in ischemic and reperfusion injuries, as it leads to glomerular vasospasm, which makes a significant contribution to the decrease in GFR in AKI 29 . In this regard, it was suggested that SGLT-2 inhibitors may increase the risk of developing AKI, which has been demonstrated in some studies 28 .…”
Section: Discussionmentioning
confidence: 99%
“…1 group - The activity of the erythropoietin mimetic peptide (pHBSP) (provided by a pharmaceutical company PHARMAPARK LLC) was studied at the doses of 5 mcg/ kg and 25 mcg/kg; the activity of infliximab (Remicade, MSD) was studied at the doses of 2 mg/kg and 10 mg/kg; the activity of recombinant erythropoietin (Epocrine, Research Institute of Highly Pure Biopreparations, Russia) was studied at the dose of 50 IU/kg; the activity of glibenclamide (Maninil, Berlin-Chemie AG, Germany) was studied at the dose of 5 mg/kg. These doses were selected based on previously identified protective effects on ischemia/reperfusion models or were calculated taking into account the recommended human doses using conversion factors (Nagata et al 2016;Kostina et al 2021;Firsova et al 2022). The dose schedule is based on the pharmacokinetic profile of the drug.…”
Section: Methodsmentioning
confidence: 99%
“…Одними из наиболее перспективных препаратов для коррекции ишемически-реперфузионной травмы почек являются эритропоэтин и его производные [1,2]. Активация гетеродимерного рецептора обуславливает развитие цитопротективных эффектов [3,4].…”
unclassified